Pengaruh Berfikir Reflektif Dan Self Confidence Terhadap Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII SMPN 9 Mataram Tahun Ajaran 2024/2025 - Apriani, Amelia; Ketut Sarjana; Ulfa Lu'luilmaknun; Nani Kurniati (Mandalika Mathematics and Educations Journal, 2025)
This study aims to determine the influence of reflective thinking and self-confidence on the mathematical problem-solving ability of grade VIII students of SMPN 9 Mataram for the 2024/2025 academic year. This research is a quantitative research with an ex-post facto (comparative causal) research method. The population of this study is 163 students in grade VIII of SMPN 9 Mataram for the 2024/2025 academic year. The sample used was 55 people who were determined using the cluster random sampling technique. The instrument in this study used a reflective thinking test in the form of description questions, self-confidence questionnaires and problem-solving ability tests in the form of description questions. The results of the study showed that there was a positive and significant relationship between reflective thinking and self confidence on the mathematical problem-solving ability of grade VIII students of SMPN 9 Mataram with a contribution of 49,9%. The results of this research are expected to be an input for teachers to develop learning that encourages students to think reflectively and build confidence in solving math problems. For students, it is important to continue to practice reflective thinking skills and increase self-confidence to support the achievement of optimal learning outcomes.